Social regulation of ageing by young workers in the honey bee, Apis mellifera - Michael Eyer (2018)
© 2016 The Authors Organisms' lifespans are modulated by both genetic and environmental factors. The lifespan of eusocial insects is determined by features of the division of labor, which itself is influenced by social regulatory mechanisms. In the honey bee, Apis mellifera, the presence of brood and of old workers carrying out foraging tasks are important social drivers of ageing, but the influence of young adult workers is unknown, as it has not been experimentally teased apart from that of brood. In this study, we test the role of young workers in the ageing of their nestmates. We measured the impact of different social contexts characterized by the absence of brood and/or young adults on the lifespan of worker nestmates in field colonies. To acquire insight into the physiological processes occurring under these contexts, we analyzed the expression of genes known to affect honey bee ageing. The data showed that young workers significantly reduced the lifespan of nestmate workers, similar to the effect of brood on its own. Differential expression of vitellogenin, major royal jelly protein-1, and methylase transferase, but not methyl farneosate epoxidase genes suggests that young workers and brood influence ageing of adult nestmate workers via different physiological pathways. We identify young workers as an essential part of the social regulation of ageing in honey bee colonies.